Promotion Strategies in Increasing Sales of Herborist Products through Social Media Instagram, Shopee and Tiktok Shop (Case Study on Herborist User Community in Muarabakti Village, Babelan, Bekasi Regency) - Tazqiatun Napsiah; Djuni Thamrin; Matdio Siahaan (SEAN Institute, 2025)
This research investigates the promotional strategies that Herborist employs to boost its sales in the digital age, focusing specifically on platforms like TikTok, Instagram, and Shopee. Utilizing a qualitative methodology, the study collects descriptive data through interviews and observations to assess the effectiveness of these strategies. The results reveal that Herborist engages consumers by creating captivating and informative content specifically designed for each social media platform, significantly influencing consumer interest and buying behaviors. Furthermore, the study underscores the critical role of consumer feedback in enhancing promotional methods and highlights the necessity for Herborist to proactively respond to customer demands and preferences. In conclusion, the findings illustrate that a cohesive and responsive promotional strategy is vital for increasing sales and building consumer loyalty within a competitive market environment.